“Porque o marido é o cabeça da mulher”: um ensaio analítico do discurso do líder religioso Edir Macedo sobre o casamento na perspectiva da semiótica Greimasiana - SILVA, Antonio Waliton Fernandes da (2022)
This paper is guided by the concepts of French semiotics for a semiotic analysis of the religious discourse of Bishop Edir Macedo taken from a video recorded at one of the meetings held in one of his churches in the context of the role of women within marriage. The purpose of this article is to understand the identity construction of the role of women in marriage in the religious conception. Greimas (1965), the creator of the theory, has been used as a theoretical contribution, as well as Diana Barros (2005) and Fiorin (1955). A qualitative approach is adopted through a bibliographic and documental research procedure. The analysis indicates that the religious discourse focused on the family environment, specifically about the role of women in marriage, is still constructed under a sexist perspective and the inferiority of the female figure compared to the male.